2018
DOI: 10.1007/s12630-018-1227-7
|View full text |Cite
|
Sign up to set email alerts
|

Humanization of critical care—psychological effects on healthcare professionals and relatives: a systematic review

Abstract: Purpose To systematically review and evaluate the effects of humanized care of the critically ill on empathy among healthcare professionals, anxiety among relatives, and burnout and compassion fatigue in both groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 80 publications
0
21
0
5
Order By: Relevance
“…The World Health Organization [WHO] (2015) defines humanization in nursing as a process of communication and mutual support between individuals, directed at transformation and understanding of the essential spirit of life. From the viewpoint of intervention in health, a recent systematic review on humanization-based intervention showed it to have substantial potential for increasing physical and emotional closeness between patient and healthcare professionals or between patients and their families (Galvin et al, 2018). From a psychological perspective, humanization refers to a style of interpersonal relations in which several psychological processes intervene, materialized in the acquisition of personal competencies (Pérez-Fuentes et al, 2019b).…”
Section: Emotional Competency and The Healthcare Humanization Constructmentioning
confidence: 99%
“…The World Health Organization [WHO] (2015) defines humanization in nursing as a process of communication and mutual support between individuals, directed at transformation and understanding of the essential spirit of life. From the viewpoint of intervention in health, a recent systematic review on humanization-based intervention showed it to have substantial potential for increasing physical and emotional closeness between patient and healthcare professionals or between patients and their families (Galvin et al, 2018). From a psychological perspective, humanization refers to a style of interpersonal relations in which several psychological processes intervene, materialized in the acquisition of personal competencies (Pérez-Fuentes et al, 2019b).…”
Section: Emotional Competency and The Healthcare Humanization Constructmentioning
confidence: 99%
“…A recent systematic review21 focused on the effect of humanised care of critically ill patients on empathy among healthcare professionals, anxiety among relatives and burnout and compassion fatigue in both groups, Galvin et al identified 12 studies addressing 4 interventions (liberal visitation, diaries, family participation in basic care and witnessed resuscitation) and 1 mixed intervention. Of 12 studies, 11 were at high risk of bias, 10 measured anxiety among 1055 relatives, 2 measured burnout in 288 ICU professionals and none addressed empathy or compassion fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Health-care providers’ well-being and mental health have received an increasing amount of attention in the last few decades [ 1 4 ]. Evidence indicates that different categories of human-care professionals (e.g., physicians and nurses) are at risk for stress-related pathology and poor well-being [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%